The influence of hydrogen peroxide concentration on the chemical kinetics of photo-accelerated tooth whitening - Costa, Joatan Lucas de Sousa Gomes [UNESP]; Nogueira, Básia Rabelo [UNESP]; Batista de Oliveira Junior, Osmir [UNESP]; Pretel, Hermes [UNESP] (Elsevier, 2022)
Background: The bleaching procedure consists of chemical principles of free radical release that react with chromophores, which results in an amount of energy released in this process. However, the evaluation of the electrical potential generated in these protocols has not yet been thoroughly investigated in the literature. Thus, this study aimed to examine variations in pH, mV, and temperature of different concentrations of hydrogen peroxide in the presence or absence of an intermittent LED/LASER photo acceleration system. Methods: The study was divided into six groups (n = 9) according to the concentration of hydrogen peroxide (6%, 15%, and 35%), associated or not with the photo acceleration system LED/LASER. We followed the variation of pH, mV, and temperature at 1, 5, 10, 15, and 30 min after gel manipulation. Data were evaluated by two-way ANOVA of repeated measures (α =0.05). Results: pH, mV, and temperature of the groups showed statistical differences both in the light and bleach and in the interaction between the two factors (p < 0.0001), where pH and mV were more influenced by the bleach and light factor, while the temperature was influenced by the bleach factor associated with light. HP15 presented the most significant change in pH, mV, and temperature. Conclusion: The use of LED/laser increased the temperature of the gels and altered the pH and mV kinetics of HP6 and HP15, which did not occur in HP35, possibly due to the high ionic potential linked to the concentration.
Keywords: Electric potential; Hydrogen peroxide; pH; Temperature; Tooth whitening; Violet LED